PEMBERIAN MAKANAN TAMBAHAN TERHADAP KEHADIRAN BALITA DI POSYANDU DESA KAMAL KECAMATAN ARJASA KABUPATEN JEMBER - Badriyah, Badriyah; Moedjiarto, Sarmini (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2012)
Malnutrition on the Indonesian infant was the main problem to get optimally healthy for infant. There were some programs to infant which made by government to rehabilitate nutrition status of infant. one of them was posyandu (integrated service post). The action of posyandu is done by cadre. The data told about presenting infant in Posyandu haven’t yet fulfilled the best target; they had problem that need the best way to solve it. The aim of this study is to determine effect of additional feeding in presenting infant at Posyandu. This was observational study by analytical method. The writer used secondary data that consist of visiting posyandu and additional feeding infant that observed by checklist. There was 80 respondents. The result showed that there was 6o infants (80%) from 80 infants are given by PMT (additional feeding), and 48 infants (80%) come to posyandu, then 12 infants (12%) didn’t come to posyandu. The result of Chi square is known by chi square count > chi square table (6,77>3,841). The analysis of chi square showed that additional feeding by self?financing could affected presenting infants in posyandu. Additional feeding self-financing is proven to support presenting infant in posyandu. The hoped from communities by awareness self in presenting infant in posyandu is daily activities to need be done therefore without additional feeding, so that Indonesian infant gets the health services optimally.Keyword: additional, feeding, presenting, Posyandu